2011
DOI: 10.4236/lce.2011.23018
|View full text |Cite
|
Sign up to set email alerts
|

Towards Green Remediation: Metal Phytoextraction and Growth Analysis of Sorghum bicolor under Different Agronomic Management

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…In sorghum treatments, a high biomass response was observed with mineral N (urea) fertilization, which was in accordance with Fellet and Marchiol (2011) and Marchiol et al (2007), who found greater biomass production in mineral‐fertilized sites (22.1 t ha −1 ) compared with organically fertilized sites (16.9 t ha −1 ). A higher biomass yield due to mineral fertilization has been explained by mineral fertilization causing a longer vegetative period, thereby delaying the senescence of the canopy (Fellet and Marchiol, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…In sorghum treatments, a high biomass response was observed with mineral N (urea) fertilization, which was in accordance with Fellet and Marchiol (2011) and Marchiol et al (2007), who found greater biomass production in mineral‐fertilized sites (22.1 t ha −1 ) compared with organically fertilized sites (16.9 t ha −1 ). A higher biomass yield due to mineral fertilization has been explained by mineral fertilization causing a longer vegetative period, thereby delaying the senescence of the canopy (Fellet and Marchiol, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…The bounded growth of leaf area due to the interference of CdCl 2 reflected in LAI depends on cell division and cell enlargement. Our results are positively correlated with the finding of (Hatamian et al 2020 andFellet andMarchiol, 2011), who reported that cadmium stress had a detrimental effect on leaf morphology due to the restricted growth of cells and their expansion (Nagajyoti and Sreekanth, 2010).…”
Section: Grain Yield Biological Yield and Harvest Indexsupporting
confidence: 91%
“…However, higher growth response was obtained in urea treatments, likely due to higher amounts of N readily available for plant uptake compared with biosolids, as discussed for ryegrass above. The high biomass response of sorghum to mineral N (urea) fertilization was in accordance with Fellet and Marchiol (2011), who suggested that higher biomass due to mineral fertilization was caused by a longer vegetative period, delaying the senescence of the canopy. In our study, however, a mineral fertilization rate of 200 kg N ha -1 resulted in a growth response similar to control treatments without N addition, carried out by Turgut et al (2005).…”
Section: Response Of Sorghum To Mineral and Organic Soil Amendmentssupporting
confidence: 80%